Influence of macroeconomic indices on European private labels - Cordero, Eloy Gil; Rondan Cataluña, Francisco Javier; Moreno, Manuel Rey (Journal of Business Economics and Management, 2016)
In this study, we have analysed the impact and evolution of some of the most important macroeconomic indices on market share and value of private labels. The originality of this paper is the linkage of macroeconomic variables of European countries and the evolution of private labels in these nations. This relationship may show the development of commercial distribution with regard to macroeconomic indices. A sample of 13 European countries and a period of 14 years have been collected, including data of private brands and macroeconomic indices. Panel Data analysis has been applied using SAS software. The percentage of female unemployment negatively affects the volume and value of private label, unlike male unemployment, which affects them positively. The GDP influences positively and slightly both the volume and the value of store brands. In addition, the fact that the percentage of urban population has a positive influence on the value of private brands but not on their volume is noteworthy. Last but not least, only the estimation of value of private label in Spain shows a significant positive increase in following years. Eight countries of the sample indicate the opposite trend.